Uptake of methylnaltrexone in Australian patients with opioid-induced constipation: a review of the number of prescriptions presented in the first 12 months of subsidisation. Issue 1 (14th November 2012) - Clark, Katherine; Rowett, Debra; Robinson, Maxine; Currow, David C
Abstract : Background: Disturbed bowel habits are very common in palliative care patients, most commonly thought to be due to opioid use. The peripheral opioid-antagonist methylnaltrexone has been subsidised in Australia to ensure that palliative care patients have timely and equitable access to this medication. The aim of this paper is to describe the use of methylnaltrexone in the first year after it was subsidised for palliative care, in particular focusing on the actual use of this medication compared with predicted need. Methods: The predicted need for methylnaltrexone was calculated using an epidemiological approach based on data collected by the Australian Institute of Health and Welfare to determine the number of Australian deaths annually. A single source of data was used to determine the number of patients who die while under the care of palliative services in Australia (National Census of Palliative Care Services, 1999). These figures allowed the number of people likely to be receiving opioids to be estimated and therefore the number who could potentially benefit from methylnaltrexone. Results: The number of patients who might benefit was calculated to be 5000, which contrasts with the 261 actual prescriptions written for methylnaltrexone. Even more striking was the disparity between initial prescriptions and the 93 requests for ongoing use. Conclusions: These data highlight much lower use of methylnaltrexone than predicted and raise a number of questions including the fact that the palliative care literature emphasises opioids as the dominant cause of constipation in palliative care patients given little ongoing use of methylnaltrexone.